Immune-Related Uncommon Adverse Events in Patients with Cancer Treated with Immunotherapy - Víctor Albarrán-Artahona; Juan-Carlos Laguna; Teresa Gorría; Javier Torres-Jiménez; Mariona Pascal; Laura Mezquita (Diagnostics, 2022)
Immunotherapy has dramatically changed the therapeutic landscape of oncology, and has become standard of care in multiple cancer types in front or late lines of therapy, with some longstanding responses and outstanding results. Notwithstanding, its use has brought a totally unique spectrum of adverse events, characterized by a myriad of diverse manifestations affecting nearly every organ and system of the body, including the endocrine, nervous, cardiac, respiratory and gastrointestinal systems. Uncommon adverse events, defined as those occurring in less than 1% of patients, comprise an even more heterogeneous group of diseases that are being seen more recurrently as the use of immune check-point inhibitors increases and indications spread in different tumor types and stages. Here, we comprehensively review some uncommon, but exceedingly important, immune-related adverse events, with special emphasis in the clinical approach and diagnostic workup, aiming to reunite the evidence published previously, allowing an increase in awareness and knowledge from all specialists implicated in the diagnosis, treatment, and care of cancer patients treated with immunotherapy.